2019
DOI: 10.1590/fst.38917
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic parameters of lipid oxidation in third generation (3G) snacks and its influence on shelf-life

Abstract: On food systems, lipid oxidation is one of the most important factors affecting food quality, nutrition, safety, color and consumer acceptance. The objective of this study was to determine the kinetic parameters of lipid oxidation and its influence in the shelf life of third generation (3G) snacks stored in three types of packaging (polyethylene, polypropylene + Kraft paper, and polyethylene + polypropylene) at 25 °C and 40 °C. The peroxide value was the quality parameter selected and monitored for a 60 day pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Dotted lines represent the model fit is presented considering rancidity and texture simultaneously.Comparing Figure8bwith 8a is possible to observe the effect of low temperatures in the rejection due to loss of crispiness (moisture increase). These results confirmed that the shelf life of fried low-moisture foods is determined by the loss of crispiness and rancidity as previous studies reported for similar products such as cassava flour-based baked products(Kulchan et al, 2010), pellets for fried snacks(Jaimez-Ordaz et al, 2019), and crackers(Manzocco et al, 2020).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Dotted lines represent the model fit is presented considering rancidity and texture simultaneously.Comparing Figure8bwith 8a is possible to observe the effect of low temperatures in the rejection due to loss of crispiness (moisture increase). These results confirmed that the shelf life of fried low-moisture foods is determined by the loss of crispiness and rancidity as previous studies reported for similar products such as cassava flour-based baked products(Kulchan et al, 2010), pellets for fried snacks(Jaimez-Ordaz et al, 2019), and crackers(Manzocco et al, 2020).…”
supporting
confidence: 90%
“…Because WBFSs are low-moisture foods, scarce research has been conducted about their shelf life (Jaimez-Ordaz et al, 2019). To the best of our knowledge, no previous reports about WBFSs' shelf life and their mathematical models have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different models were applied to fit the experimental data to obtain information about the changes produced in the quality attributes of the ACWW during storage. Initially, they were fitted with the zero-and first-order kinetic models (Dermesonlouoglou et al, 2016;Jaimez-Ordaz et al, 2019;Park et al, 2018).…”
Section: Kinetic Considerationsmentioning
confidence: 99%
“…Consequently, a reliable kinetic model is often needed. While there have been studies of the kinetics of the lipid peroxidation ( 19 , 20 ) of vegetable oils and of biodiesel fuel ( 21 ) production from vegetable oils, the kinetics of sesamin conversion in a sesame oil system have not been studies. One research group noticed that the kinetics of sesamin conversion is of first-order in the ethanol-sesamin system by using hydrochloric acid as a catalyst ( 22 ).…”
Section: Introductionmentioning
confidence: 99%